2022
DOI: 10.1007/jhep03(2022)017
|View full text |Cite
|
Sign up to set email alerts
|

Constraining $$ \mathcal{CP} $$-violation in the Higgs-top-quark interaction using machine-learning-based inference

Abstract: While $$ \mathcal{CP} $$ CP violation in the Higgs interactions with massive vector boson is already tightly constrained, the $$ \mathcal{CP} $$ CP nature of the Higgs interactions with fermions is far less constrained. In this work, we assess the potential of machine-learning-based inference methods to constrain $$ \mathcal{CP} $$ CP violation in the Higgs top-Yukawa coupling. This approach enables the use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…In the left panel we consider t t H production to constrain the two SMEFT Wilson coefficients c u and c G . In the right panel we consider the same process to constrain CP-violation in the top-Higgs coupling, as parameterized by the magnitude κ t and CP-phase α of the top Yukawa coupling [116,121].…”
Section: Madminermentioning
confidence: 99%
“…In the left panel we consider t t H production to constrain the two SMEFT Wilson coefficients c u and c G . In the right panel we consider the same process to constrain CP-violation in the top-Higgs coupling, as parameterized by the magnitude κ t and CP-phase α of the top Yukawa coupling [116,121].…”
Section: Madminermentioning
confidence: 99%
“…In the left panel we consider t t H production to constrain the two SMEFT Wilson coefficients c u and c G . In the right panel we consider the same process to constrain CP-violation in the top-Higgs coupling, as parameterized by the magnitude κ t and CP-phase α of the top Yukawa coupling [115,120].…”
Section: Madminermentioning
confidence: 99%
“…First phenomenological studies on synthetic data have shown that these methods have the potential to substantially improve the precision of Higgs measurements at the LHC [165,166,167,185,186,187,188]. It remains a challenge to scale these analyses to real data and in particular to a realistic modeling of systematic uncertainties, which are usually modeled with thousands of nuisance parameters.…”
Section: Examplesmentioning
confidence: 99%